2011
DOI: 10.1074/jbc.m110.101527
|View full text |Cite
|
Sign up to set email alerts
|

Functional Gene Expression Profiling in Yeast Implicates Translational Dysfunction in Mutant Huntingtin Toxicity

Abstract: Huntington disease (HD) is a neurodegenerative disorder caused by the expansion of a polyglutamine tract in the huntingtin (htt) protein. To uncover candidate therapeutic targets and networks involved in pathogenesis, we integrated gene expression profiling and functional genetic screening to identify genes critical for mutant htt toxicity in yeast. Using mRNA profiling, we have identified genes differentially expressed in wild-type yeast in response to mutant htt toxicity as well as in three toxicity suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 51 publications
(68 reference statements)
5
51
0
Order By: Relevance
“…RNA processing has been previously implicated in HD based on several expression profiling studies in cells, mouse, yeast and fly models of HD. [72][73][74][75][76] These studies demonstrate enrichment in ribosomal and RNA-processing proteins. In line with this, we showed that expanded Htt complexes were enriched in proteins related to RNA processing and regulation of translation and identified several novel Htt interactors within these pathways.…”
Section: Discussionmentioning
confidence: 74%
“…RNA processing has been previously implicated in HD based on several expression profiling studies in cells, mouse, yeast and fly models of HD. [72][73][74][75][76] These studies demonstrate enrichment in ribosomal and RNA-processing proteins. In line with this, we showed that expanded Htt complexes were enriched in proteins related to RNA processing and regulation of translation and identified several novel Htt interactors within these pathways.…”
Section: Discussionmentioning
confidence: 74%
“…4b, compare the upper and lower FLAG blots). Translation factors have a modifying effect on the aggregation and toxicity of N-terminal fragment-based models of mutant Htt toxicity in Caenorhabditis elegans and Saccharomyces cerevisiae (52,53). The differences in sedimentation profiles, mass spectrometry-identified protein associations, and the modifying effect that translation proteins have on mutant Htt toxicity in model systems suggest that mutant Htt may affect translation.…”
Section: ϫ10mentioning
confidence: 99%
“…Translation or transcription might be attenuated to decrease the flux of incoming nascent proteins to accommodate the lower rate of ERAD in these cells. In yeast, translational dysfunction has been observed coincident with mHtt ex1 expression (Tauber et al, 2011). For diseases such as HD, the inability of cells to cope with ER stress could represent an important modulator of the mutant protein toxicity.…”
Section: Journal Of Cell Science 124 (19) 3340mentioning
confidence: 99%